Penanganan Perkara Menguasai Tanah Tanpa Izin: Studi Putusan Mahkamah Agung Nomor 1091 K/Pdt/2021 - Zahra, Dania; Ikhsan, Edy; Kaban, Maria (AL-SULTHANIYAH, 2025)
This study discusses the land ownership trial between Defendant I, Defendant II, and Defendant III based on the Decision of the Pematang Siantar District Court Number 81/Pdt.G/2019/PN PMS. This dispute gives rise to different interpretations of the validity of the Kotapradja Letter which is used as evidence of land ownership. This study uses a normative legal method with a descriptive analytical nature, a normative approach, and secondary data collected through document studies, analyzed qualitatively. The results of the study indicate that the validity of the Kotapradja Letter is weak because after the enactment of the Basic Agrarian Law (UUPA), all land certificates must be re-registered to obtain strong legality. At the first level, the panel of judges granted the plaintiff's lawsuit based on documentary evidence and witness statements. However, at the appeal level, the defendant succeeded in overturning the initial decision with additional evidence. The case brought to the Supreme Court showed that SHM 326 of 1995 belonging to the plaintiff and SHM 0042 of 1984 belonging to Defendant I were in accordance with the measurement results, so that the land controlled by Defendant I was legally valid. This study emphasizes the importance of legal certainty in maintaining land and the need to verify the legality of documents to prevent ownership conflicts.